Pragmatyczne mechanizmy składni języka mówionego - Labocha, Janina (Slavia Occidentalis, 2012)
In her book Składnia rozmowy telefonicznej (“Syntax of Telephone Conversations”) Krystyna Pisarkowa presents syntactical structures of a simple and compound sentences appearing in spoken dialogues and discusses their pragmatic conditions. Moreover, she devotes attention to lexical indicators of segmentation of a spoken text and the expressions performing phatic and connotative functions. In many places in the book the author provides inspiring instructions for researchers studying the structure of a spoken text.